Distinctive Features Of Didactic Songs In Khorezm Vocal Art - Daniyorbek Obidov (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
This article provides a scholarly analysis of the genre characteristics, poetic structure, and educational functions of didactic songs formed within the framework of the Khorezm musical style. Particular attention is paid to musical and performance-related features specific to the Khorezm tradition, such as melody, pronunciation, and modal-rhythmic structures.